If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4x + -2 = 6 Reorder the terms: -2 + 0.4x = 6 Solving -2 + 0.4x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 0.4x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 0.4x = 6 + 2 0.4x = 6 + 2 Combine like terms: 6 + 2 = 8 0.4x = 8 Divide each side by '0.4'. x = 20 Simplifying x = 20
| f(x)=-0.06(x-0)(x-75) | | (2x^5/25)(5/5x^9) | | 2x+x=x+3-y | | -97w-14=-656 | | 4t-2+2t=6+t | | 12x-14=3x+1 | | y=.66x-1 | | -4p-3(4+p)=-7p-12 | | 5(n+4)=4n+23 | | 4y+18= | | -189=-5x+7(-4x+6) | | 2c-(-4c+20)=-2 | | 2/15x=4/5 | | cos^2x=cosx+1 | | 6x-(-13)=-68+3x | | y(x^2+9)+8(x^2+9)=0 | | 600=(12v^2)/2 | | 6(6q-4)= | | 16(10)+10y=500 | | x/100=140/150 | | 16(12)+10y=500 | | -9=a+-3 | | 6=-2r+6+2r | | 16(40)+10y=500 | | .25(x-12)=12 | | -4=-7r+7r | | -m+m=0 | | 3x^2y-5xy+4y=0 | | 33=3(5x-1)-6x | | 16(15)+10y=500 | | 2(2)+y=8 | | (2x-3)(x-2)=(x+1)(x-2)+3 |